Combination of simulated annealing and pseudo spectral methods for the optimum removal rate in turning operations of nickel-based alloys. (January 2018) - Palacios, J.A.; Olvera, D.; Urbikain, G.; Elías-Zúñiga, A.; Martínez-Romero, O.; López de Lacalle, L.N.; Rodríguez, C.; Martínez-Alfaro, H.
Highlights: A creative combination of semi discretization methods with simulated annealing, to accelerate the computation time in a real industrial problem. Reduction in time to find good combinations of rotational speed and depth of cut. Experimental test were performed matches model results. SNMG inserts, in turning operations of superalloys such as Inconel® 718, allows a material removal rate greater than that obtained by using the VBMT insert. Abstract: In this paper, an approach that combines simulated annealing technique (SA) with the Chebyshev collocation method (CCM) or with the Enhanced Multistage Homotopy Perturbation (EMHPM) is established. Then, these two new approaches are applied to find optimal cutting conditions in turning operations of nickel-based superalloy (Inconel 718©) by using SNMG and VBMT tool-inserts. To validate the proposed approaches in terms of material removal rate and stability, a series of turning cutting tests were carried out. Numerical results show that when the CCM is combined with SA technique, the optimum stable cutting conditions such as the axial depth of cut and the spindle speed, were estimated 100 times faster than from the CCM. Furthermore, experimental data and numerical results confirmed that the productivity by using a tool-SNMG insert is 19% higher than when using VBMT tool-insert, which is mainly due to the tool stability dynamic response.